2022
DOI: 10.1155/2022/6707821
|View full text |Cite
|
Sign up to set email alerts
|

Linc00312 Single Nucleotide Polymorphism as Biomarker for Chemoradiotherapy Induced Hematotoxicity in Nasopharyngeal Carcinoma Patients

Abstract: Background. Linc00312 is downregulated in nasopharyngeal carcinoma (NPC) and associates with poor treatment efficacy. Genetic variations are the main cause of individual differences in treatment response. The objective of this study is to explore the relationship between genetic variations of linc00312 and the risk of chemoradiotherapy induced toxic reactions in NPC patients. Methods. We used a bioinformatics approach to select 3 single nucleotide polymorphisms (SNPs) with regulatory feature in linc00312 (rs12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Previous study has reported lncRNA GAS5 rs2067079 (C > T) could affect the secondary structure of GAS5 and was associated with an obviously increased risk of radio-chemotherapy induced hematotoxicities in NPC patients 36 . In addition, linc00312 rs12497104 (G > A) could destroy the binding between mir-411-3p and linc00312, and affect the expression of linc00312, thus conferring increased susceptibility risk and poorer overall survival in NPC patients 29 , 37 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous study has reported lncRNA GAS5 rs2067079 (C > T) could affect the secondary structure of GAS5 and was associated with an obviously increased risk of radio-chemotherapy induced hematotoxicities in NPC patients 36 . In addition, linc00312 rs12497104 (G > A) could destroy the binding between mir-411-3p and linc00312, and affect the expression of linc00312, thus conferring increased susceptibility risk and poorer overall survival in NPC patients 29 , 37 .…”
Section: Discussionmentioning
confidence: 99%
“…Two loci located within the LINC00312 gene (rs12497104 and rs164966) were chosen for analysis in this study on the basis of their putative association with nasopharyngeal carcinoma susceptibility 21 , 23 . The QIAamp DNA Blood Mini Kit (Qiagen) was used to extract genomic DNA from whole blood specimens.…”
Section: Methodsmentioning
confidence: 99%
“…Specifically, LINC00312 variants, rs15734 and rs164966, were associated with a decrease in the risks of developing NPC, as patients with rs12497104 polymorphisms showed a poorer overall survival [21,22]. In addition, association of rs12497104 and rs15734 with chemoradiotherapy-induced hematotoxicity in NPC was recently reported [23]. As LINC00312 was found to be implicated in the development of oral submucous fibrosis [24] and head and neck cancer [25], the impact of LINC00312 SNPs together with lifestyle-related risks on OSCC is in need of clarification.…”
Section: Ivyspringmentioning
confidence: 97%
“…Linc00312 exhibits dysregulation and reduced expression in NPC, linked to its role in NPC progression, drug resistance, short-term efficacy, and OS ( 70 ). Upregulating Linc00312 enhances NPC sensitivity to radiotherapy by inhibiting radiation-induced signal transduction pathways and DNA damage repair–related protein expression ( 29 , 30 ). Aberrant expression of PTPRG-AS1, observed in various malignant tumors, including NPC, demonstrates its effect on radiosensitivity.…”
Section: Role Of Lncrna In Npc Radiotherapy Resistancementioning
confidence: 99%